2024
DOI: 10.1039/d3sc06864a
|View full text |Cite
|
Sign up to set email alerts
|

Boryls, their compounds and reactivity: a structure and bonding perspective

Xueying Guo,
Zhenyang Lin

Abstract: Boryls and their compounds are important due to their diverse range of applications in fields of materials science and catalysis. They are integral part of boron chemistry, which has attracted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Transition metal (TM) boryl complexes were first proposed in the 1960s by the group of Nöth from the salt metathesis of haloboranes with Na­[Mn­(CO) 4 L] (L = CO, PPh 3 ) and Na­[CpFe­(CO) 2 ] (Cp = C 5 H 5 ) . It was not until 1990, however, that TM boryl complexes were first structurally characterized, in both cases featuring a covalent Ir–B bond resulting from the oxidative addition of a borane B–H bond at a trigonal bipyramidal PMe 3 -stabilized Ir­(I) precursor. , From then on, the field expanded rapidly, fueled in particular by the commercial availability of air-stable boronic and diboron esters, such as HBCat and B 2 Cat 2 (Cat = catecholato), and the key role of TM boryl complexes as intermediates in numerous catalytic reactions, including borylations, diborations, and hydroborations. Computational and experimental studies have shown that metal–boron bonding in TM boryl complexes is mainly covalent, characterized by very strong B→M σ donation and only a small contribution of M→B π donation into the empty p z orbital at boron. As a result, boryl ligands induce some of the strongest trans influence, which may be used to enhance catalytic activity. …”
Section: Introductionmentioning
confidence: 99%
“…Transition metal (TM) boryl complexes were first proposed in the 1960s by the group of Nöth from the salt metathesis of haloboranes with Na­[Mn­(CO) 4 L] (L = CO, PPh 3 ) and Na­[CpFe­(CO) 2 ] (Cp = C 5 H 5 ) . It was not until 1990, however, that TM boryl complexes were first structurally characterized, in both cases featuring a covalent Ir–B bond resulting from the oxidative addition of a borane B–H bond at a trigonal bipyramidal PMe 3 -stabilized Ir­(I) precursor. , From then on, the field expanded rapidly, fueled in particular by the commercial availability of air-stable boronic and diboron esters, such as HBCat and B 2 Cat 2 (Cat = catecholato), and the key role of TM boryl complexes as intermediates in numerous catalytic reactions, including borylations, diborations, and hydroborations. Computational and experimental studies have shown that metal–boron bonding in TM boryl complexes is mainly covalent, characterized by very strong B→M σ donation and only a small contribution of M→B π donation into the empty p z orbital at boron. As a result, boryl ligands induce some of the strongest trans influence, which may be used to enhance catalytic activity. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, spontaneous homolytic B–B bond cleavage is an alternative approach to obtaining boryl radicals. However, this alternative strategy is hard to realize in diboron(4) systems, as most observed reactions of diboron(4) were often initiated by the coordination of substrate molecules followed by a series of two-electron processes . Furthermore, two-coordinated boryl radicals, resulting from a homolytic B–B bond cleavage of diborane(4) species, are highly reactive and difficult to isolate because of the pronounced electron deficiency at the boron centers. Thus, we envisioned that a diboron(6) dianion could be a suitable motif for promoting homolytic B–B bond cleavage because the two boron centers are tetra-coordinated, and examples of such boryl radical anions were known .…”
Section: Introductionmentioning
confidence: 99%
“…However, the synthesis and utilization of Bpin-BF 3 M salts have remained relatively obscure, and no reports, to the best of our knowledge, address their exploration (Figure 2). 1,2,17,18 Therefore, it is imperative that a new general, mild, and diversifiable method for Bpin-BF 3 M salts be developed. 18 With this goal in mind, we envisioned an operationally simple strategy to synthesize Bpin-BF 3 M salts 11a and convert them into valuable unsymmetrical diboron motifs (12) through the trifluoroborate (BF 3 ) moiety transformation.…”
mentioning
confidence: 99%
“…It is worth noting that these unsymmetrical diborons, specifically 11, 12a, 12c, 12e, 13a, 14a, and 14b, belong to a family of compounds that currently face challenges in terms of efficient synthetic access. 1,2,17,27,28 In conclusion, we have developed a novel masking strategy achieved through the initial desymmetrization of diboron(4) compounds employing nucleophilic trifluorination. This approach facilitates the transformation of symmetrical diboron structures into unsymmetrical diborons.…”
mentioning
confidence: 99%
See 1 more Smart Citation